A CASE STUDY ON INTERCULTURAL PROCESS IN LIMITED SETTING - Trihastutie, Nopita (Faculty of Letters, Dr. Soetomo University, 2017)
In a global world, living in other country is no longer unusual thing. Thus, the encounter with other culture is unavoidable. Progressing from ethnocentrism to ethno-relativism is vital for the success of someone living out of his/her mother country. This progress occurs through an intercultural process. A study on the intercultural process utilizes short self-reports and surveys to conduct the assessments of individualsâ€™ attitude, personalities, and values. Â Conducted in an informal school with a boarding system, this study examines how the intercultural process of foreign teachers and whether this process gives influence to the local studentsâ€™ cross cultural understanding. An informal school with a boarding system is a limited setting for an intercultural process. However, the interaction is still considered natural for two reasons: firstly, no certain particular cultural obligation for personal and social conduct there; secondly, cultural â€œtake and giveâ€ occurs. The process occurs to both foreign teachers and local students. To some extent, the intercultural process of one party contributes the other partyâ€™s cross cultural understanding.Key Words: Intercultural Process, Cross Cultural Understanding